Seroprevalence of Hepatitis B and Hepatitis C Virus in HIV/AIDS Patients at Gaziantep University - Ahmet Şahin; Sema Şahin; Mustafa Namıduru; İlkay Karaoğlan; Vuslat Boşnak (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2016)
Introduction: Human immunodeficiency virus (HIV) or acquired immune deficiency syndrome (AIDS) have major effect on the morbidity and mortality related with hepatitis B (HBV) and C virus (HCV) infections. Several observational studies suggest that HIV/HBV and HIV/HCV coinfected patients may have higher rates of fibrosis progression and an increased risk of cirrhosis, end-stage liver disease, and hepatocellular carcinoma than patients with HBV and HCV infection alone. Hepatocellular carcinoma also occurs at an earlier age among HIV-infected patients compared to HIV-seronegative patients. In our study, we aimed to investigate the seroprevalence of HBV and HCV co-infections because of common transmission route in patients with HIV/AIDS. Materials and Methods: We retrospectively evaluated 113 HIV/AIDS patients followed by the Infectious Diseases and Clinical Microbiology Clinic at Gaziantep University Şahinbey Training and Application Hospital between 2011 and 2016. Demographic data of patients, HIV transmission routes, enzyme-linked immunosorbent assay results of HBV surface antigen (HBsAg), anti-HBsAg, anti-HBcAg immunoglobulin (Ig) total and anti-HCV serology, and real-time polymerase chain reaction results of serum HBV DNA and HCV RNA levels were obtained from patient records. Results: Ninety-four (83.2%) of 113 HIV/AIDS patients were male and 19 (16.8%) were female. The average age of the patients was 40.22±11.41 years. Eight patients (7%) were positive for HBsAg, 31 (27-4%) for anti-HBcAg total Ig, six (5%) for isolated anti-HBcAg Ig total 47 (41.5%) for anti-HBsAg and three (2.6%) subjects were positive for anti-HCV. All patients who were exposed to HBV were heterosexual. Of the three patients exposed to HCV, two (66.6%) were intravenous drug user. Symptoms of cirrhosis were not observed in HIV/HBV co-infected patients, while one HIV/HCV co-infected patient but one HIV/HCV co-infected patient. Conclusion: Because of the common transmission routes of HBV, HCV and HIV, serologic and virologic markers of hepatitis are necessary for both diagnosis and treatment of co-infections. Co-infection affects chronic hepatitis progression. This is important to avoid possible complications such as cirrhosis. Therefore, all patients with HIV infection should be followed for HBV and HCV.